Prospects for the study of the strangeness and hypernuclei production at NICA/MPD. (November 2019) - Zinchenko, A; Kolesnikov, V; Mudrokh, A; Vasendina, V; Voronyuk, V
Abstract: The prospects for the study of the strangeness and hypenuclei production with the MultiPurpose Detector (MPD) at NICA are presented and the detector performance for such physics analyses, evaluated from the Monte Carlo simulation, are demonstrated.